Learning of National Identity in Areas of Conflict: The Case of Greek-Cypriot Young Adults in Cyprus - Christos Anagiotos; Fred M. Schied (Adult Education Research Conference, 2013)
Cyprus is a divided country as a result of nationalist conflict. Greek-Cypriots and Turkish-Cypriots have lived apart since 1974. This phenomenological study aims to describe how Greek-Cypriot young adults (born after 1974) make sense of their national identity and how their experiences have influenced the learning and construction of their national identity